2017
DOI: 10.1002/kpm.1540
|View full text |Cite
|
Sign up to set email alerts
|

Health and Safety Culture as a Competitive Advantage for Knowledge‐based Organizations: An HSEC Model Perspective

Abstract: Because knowledge is increasingly considered to be a key resource for companies, organizations must create and foster knowledge-sharing culture. A clear plan and strategy for knowledge creating, sharing it, and managing it provides sustainable competitive advantages for knowledge-based organizations. Knowledge as an important source of capital for an organization can only be created and managed properly and successfully in a healthy cultural environment. The knowledge stores of organizations are in the minds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…Safety culture has been deemed a critical developmental component of health and safety regimes within social services (Firoozi and Hatami, 2017; Mellor and Webster, 2013). However, scant empirical inquiry has been directed at exploring how safety culture in an organization supports factors related to health and safety.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Safety culture has been deemed a critical developmental component of health and safety regimes within social services (Firoozi and Hatami, 2017; Mellor and Webster, 2013). However, scant empirical inquiry has been directed at exploring how safety culture in an organization supports factors related to health and safety.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Mellor and Webster (2013) advocate the use of consistent management practices supporting safety, such as work planning, pro-safety interactions, appropriate resourcing, and self-assessment, while DeJoy (2005) calls for the creation of data and evaluation tools for health and safety programs. Broadly, successful health and safety models are conceptualized as managing complexity and uncertainty in an organization, including gaining a deep understanding of health and safety culture to determine key hazards and risks (Firoozi and Hatami, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was conducted in the Korean context with a focus on sustainable performance and not competitiveness. Naser and Akram, (2017) Health and Safety Culture as a Competitive Advantage for Knowledge based Organizations: An HSEC Model Perspective. This study employed the health, safety, environment, and culture (HSEC) model as a managerial tool to help managers create a health and safety culture for creating and managing knowledge and also gain a real competitive advantage in this highly competitive era.…”
Section: Safety Health Environment and Competitivenessmentioning
confidence: 99%
“…It turns out that safety knowledge and safety motivation are key factors in interpreting these relationships. Firoozi et al [ 26 ] found that knowledge is an important source of capital for an organization and can only be correctly created and managed in a healthy cultural environment. The paper adopts a health, safety, environment and cultural model as a management model, which enables people to have a deep understanding of the health and safety culture that promotes the interaction and transformation process.…”
Section: Introductionmentioning
confidence: 99%